Odpowiedzi

2010-01-23T16:53:54+01:00
A) 8xyz
b) 1a²b
c) 4xy
d) -⅓abc
e) - 30xy
f) - 2x⁴
Najlepsza Odpowiedź!
2010-01-23T17:06:24+01:00
A) -4 * x * y * (-2) * z = -4x * y *(-2) * z = - 4xy * (-2) * z = 8xy * z = 8xyz
b) -a * 2 * b* ½ * (-a) = - 2a * b * 1/2 * (-a) = -2ab * 1/2 * (-a) = -ab * (-a) = a²b
c) 8 * x * (-2) * y * (-1/4) = 8x * (-2) * y * (-1/4) = -16xy * (-1/4) = 4xy
d) -a * (-b) * c * (-1/3) = ab * c * (-1/3) = abc * (-1/3) = -1/3 abc
e) x * (-3) * (-2) * y * (-5) = -3x * (-2) *y * (-5) = 6xy * (-5) = -30xy
f) x * 2x * 0,5 * (-2) * x² = 2x² * 0,5 * (-2)x² = x² * (-2x²) = -2x⁴